A Biomedical Informatics Perspective on Human Factors - How Human Factors Influence Information Technology Adoption - Meyer, R.; Section Editor for the IMIA Yearbook Section on Human Factors (Yearbook of Medical Informatics, 2011)
to select and summarize excellent research published in 2010 in the field of bio-medical informatics human factors.we attempt to derive a synthetic overview of the activity and new trends in this field, from a selection of worldwide research papers published during 2010.this year again, healthcare information technology (HIT) adoption occupies a central role in the field and leads to research focused mainly on measuring impact and factors influencing it. One of the selected papers especially dissects the anatomy of a nationwide personal electronic health record adoption failure.Due to the vast and increasing amount of excellent works, choosing the best papers in human factors is a challenge. More and more the published work takes into account fundamental principles expressed in Grudin’s Laws, one form of which is: “When those who beneût from a technology are not those who do the work, then the technology is likely to fail or be subverted.”.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; human factors